Imaging in patients with ST-segment elevation myocardial infarction - a case report - Gniot, Marcelina; Jankiewicz, Marek (Journal of Education, Health and Sport, 2023)
Introduction and purpose: Intravascular ultrasound (IVUS) facilitates 3-dimensional visualization of the blood vessels. Nowadays, it becomes increasingly supportive in percutaneous coronary intervention (PCI) guiding in patients with acute myocardial infarction (AMI). This report presents IVUS-guided PCI performed on 43-year-old patient with ST-segment elevation myocardial infarction (STEMI). Brief description of the state of knowledge: IVUS is an established intracoronary imaging technique that can be used in patients with AMI. It allows assessment of the plaque nature, stent selection and optmisation. An increasing body of evidence shows that IVUS-guided PCI is correlated with reduction in number of major adverse cardiovascular events (MACE), stent thrombosis and with less contrast use. Studies show, that IVUS can be used in patient with STEMI, as it is presented in this report. Conclusion: This case illustrates IVUS-guided PCI performed on the patient with STEMI. It shows that it is crucial to consider using this technique in every patient with AMI, as it provides beneficial outcome of the treatment. It is particularly important in patients with complicated anatomy of the blood vessels and in patients with contraindications to the considerable contrast use.